PENGARUH KINERJA KEUANGAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2015-2018 - Mimelientesa Irman; Sherin Tanili; Haugesti Diana; Linda Hetri Suriyanti (Journal Of Islamic Finance And Accounting Research, 2022)
The purpose of this research is to examine the effect of Financial Performance and Capital Structure to Firm Value in which Firm Size as moderating variable. Population of this research is 46 mining companies listed in Indonesia Stock Exchange period of 2015-2018. While the samples are 29 companies by using the purposive sampling method. The data analysis technique used is partial least square regression. The result of this research indicate that Financial Performance and Capital Structure have a positive effect on Firm Value. Firm Size cannot moderate the influence of Financial Performance and Capital Structure on the Firm Value.